Prognostic Value of Tumor Regression Grading in Patients Treated With Neoadjuvant Chemotherapy Plus Surgery for Gastric Cancer - Xie, Jian-Wei; Lu, Jun; Xu, Bin-bin; Zheng, Chao-Hui; Li, Ping; Wang, Jia-Bin; Lin, Jian-Xian; Chen, Qi-Yue; Cao, Long-Long; Lin, Mi; Tu, Ru-Hong; Huang, Ze-Ning; et al. (Frontiers in Oncology, 2021)
Objective: To validate the prognostic value of tumor regression grading (TRG) and to explore the associated factors of TRG for advanced gastric cancer (AGC) with neoadjuvant chemotherapy (NACT) plus surgery. Methods: Two hundred forty-nine AGC patients treated with NACT followed by gastrectomy at the Mayo Clinic, USA and the Fujian Medical University Union Hospital, China between January 2000 and December 2016 were enrolled in this study. Cox regression was used to identify covariates associated with overall survival (OS) and recurrence-free survival (RFS). Logistic regression was used to reveal factors predicting tumor regression grading. Results: For patients with TRG 0-1, the 3- and 5-year OS rates were 85.2% and 74.5%, respectively, when compared to 56.1% and 44.1% in patients with TRG 2 and 28.2% and 23.0% in patients with TRG 3, respectively (p<0.001). TRGs were independent risk factors for OS. Similar findings were observed in RFS. Multivariable analysis revealed that an oxaliplatin-based regimen (p=0.017) was an independent predictor of TRG. The oxaliplatin-based regimen was superior to the nonoxaliplatin-based regimen for OS (38.4 months vs 19.5 months, respectively; p=0.01). Subgroup analyses by histological subtype indicated that the oxaliplatin-based regimen improved the OS in nonsignet ring cell carcinoma compared to the nonoxaliplatin-based regimen (53.7 months vs 19.5 months, respectively; p=0.011). However, Similar findings were not observed in RFS. Conclusion: TRG was an independent factor of AGC treated with neoadjuvant chemotherapy plus surgery. Oxaliplatin-based neoadjuvant chemotherapy regimens improve tumor response and may have an overall survival benefit for patients with nonsignet ring cell carcinoma.